Basic Operations on Vedic Mathematics: A Study on Special Parts - Parajuli, Krishna Kanta (Nepal Journal of Mathematical Sciences, 2020)
Vedic Mathematics was rediscovered and reconstructed by Sri Bharati Krishna Tirthaji from ancient Sanskrit texts Veda early last century between 1911 – 1918 is popularly known today is Vedic Mathematics. It is an extremely refined, independent and efficient mathematical system based on his 16 formulae and some sub-formulae with simple rules and principles. The main purpose of this paper is to communicate a new approach to Mathematics, offering simple, direct, one-line, mental solutions to mathematical problems. In the way of basic mathematical operations like addition, subtraction, multiplication and division can be done in simple ways, and results are obtained quickly and can be checked in a minute by using the Vedic techniques. In this system, for any problem, there is always one general technique and also some special pattern problems. This paper especially concentrates only on the specific pattern of elementary operation of Vedic Mathematics.